2010
DOI: 10.1111/j.1365-2125.2009.03596.x
|View full text |Cite
|
Sign up to set email alerts
|

Drugs and dilated cardiomyopathies: a case/noncase study in the French PharmacoVigilance Database

Abstract: WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Dilated cardiomyopathy is a frequent disease, responsible for 40–50% of cases of heart failure. • Several aetiologies have been reported: idiopathic, familial/genetic, viral and/or immune but also toxic agents (alcohol, cobalt, carbon monoxide, lead, cocaine, mercury or drugs). • Among drugs, anthracyclines are well known to induce such an adverse drug reaction. WHAT THIS STUDY ADDS • This study describes an association with already suspected drugs (anthracyclines,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 32 publications
0
31
0
1
Order By: Relevance
“…Thus, the case/noncase method is a very useful method for assessing and detecting associations between a specific adverse drug effect and exposure to drugs in real conditions of use, because it is simple and quick and the data used are already available. Several studies have been recently published using this method on this database applying to different fields of drug safety [3,8] but also to pharmacodependence [9].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the case/noncase method is a very useful method for assessing and detecting associations between a specific adverse drug effect and exposure to drugs in real conditions of use, because it is simple and quick and the data used are already available. Several studies have been recently published using this method on this database applying to different fields of drug safety [3,8] but also to pharmacodependence [9].…”
Section: Discussionmentioning
confidence: 99%
“…Among the remaining papers, 6 were not eligible because they did not use populationbased samples, 2 papers were concerned with neurobiology and (or) pathophysiology, and 7 were pharmacovigilance reports. [10][11][12][13][14][15][16] The remaining 26 papers were concerned with topics not relevant to the review. Finally, one additional paper that was published after completion of the review was included because it reported Canadian data.…”
Section: Methodsmentioning
confidence: 99%
“…Less frequently, it could be related to some toxic agents or drugs. A case-noncase study using the French PharmacoVigilance database was able to describe an association with some already suspected drugs (such as anthracyclines and antiretrovirals), but also with other drugs (antipsychotics, lithium, antidepressants and retinoids) less known to induce such an ADR [9]. This finding represents a pharmacovigilance signal which needs to be investigated by future prospective studies.…”
Section: Drug Of Interest (X)mentioning
confidence: 99%